Traditionalist identity pattern in inheritance among Serbs in the north of Kosovo and Metohija – The case оf the city of Kosovska Mitrovica - Vučković, Branislava (Sociološki pregled, 2025)
Nowadays, the power relations in Kosovo and Metohija have placed the Serbian community in a marginalized position, and this is exactly the type of social groups whose memory, as opposed to the official one and as an expression of the desire to preserve one’s own identity in a hostile environment, was the subject of research that constituted the culture of remembrance as a discipline. Collective memory is constituted in the dialectic of remembering and forgetting. The memory of marginalized groups as an essential element of their identity is simultaneously opposed to the official politics of remembrance. Starting from the classification of the forms of forgetting offered by Aleida Assmann, we try to explain the ways, but also the causes and potential consequences of imposing the oblivion of Serbian culture in Kosovo and Metohija.